Enhancing Schoolchildren’s Enterobiasis Prevention Through Booklet-Based Health Educatioan - Wint Aung, Hnin; Tun, HtetMyat (Journal of Health Innovation and Environmental Education, 2026)
Purpose of the study: This study aims to examine the effect of booklet-based health education on fifth-grade students’ knowledge and preventive behaviors regarding Enterobius vermicularis at Primary School Ye Twin Kaung, Ye Twin Kaung Village, Sagaing. The study focuses on assessing whether visual and verbal educational materials can improve hygiene practices to prevent pinworm infection.Methodology: A pre-experimental one-group pretest–posttest design was applied. Participants were 11 fifth-grade students selected by purposive sampling. Data were collected using structured knowledge questionnaires and observation checklists. The intervention consisted of a 30-minute booklet-based health education session with visual illustrations and verbal explanations. Data were analyzed using the Wilcoxon Signed-Rank Test.Main Findings: Booklet-based health education significantly improved students’ knowledge and preventive behaviors against Enterobius vermicularis. Knowledge levels increased from 9.1% to 90.9% for good knowledge, while good preventive behaviors rose from 18.2% to 81.8%. The intervention effectively translated understanding into observable hygiene practices, such as handwashing and avoiding soil contact, within three days post-intervention.Novelty/Originality of this study: This study introduces a visually engaging, age-appropriate booklet combined with facilitator-led discussion to improve both knowledge and practical preventive behaviors in elementary school children. Unlike prior research relying on static or passive educational materials, this intervention links cognitive understanding directly to action, offering a novel, sustainable approach for school-based enterobiasis prevention programs.